Consumption of sheep milk compared to cow milk can affect trabecular bone ultrastructure in a rat model. Issue 1 (5th December 2018) - Burrow, Keegan; Young, Wayne; Carne, Alan; McConnell, Michelle; Hammer, Niels; Scholze, Mario; Bekhit, Alaa El-Din
Abstract : Sheep milk contains a higher nutrient content compared to cow milk and is able to improve the structure of bone. Abstract : Cow milk has a positive effect on bone health due to the effects of its protein, fat, lipid, vitamin, and mineral components. Sheep milk contains a unique composition of all of these components. However, to the best of our knowledge the benefits of sheep milk in relation to bone development have not been studied. The aim of the present study was to determine the effects of the consumption of sheep milk in comparison to cow milk on the structural and physical characteristics of growing bone in a rat model. Newly weaned male rats were fed either cow milk, sheep milk or sheep milk diluted to the same total solids content as cow milk for 28 days in addition to a basal chow. At the end of the feeding period animals were euthanized, the femora harvested and stored. The femora were analysed by μ-CT, mechanical bending tests, and ICP-MS. Rats consuming sheep milk in the trial were found to have significantly higher trabecular bone surface density and trabecular bone surface to volume ratio ( p < 0.05) when compared to the rats consuming cow milk. No significant differences were observed in the mechanical properties and the mineral composition of the bones ( p > 0.05). With the exception of Rb, which was found to be present in higher concentrations in rats consuming sheep milk ( p < 0.05). Our results indicate that consumption of sheep milk may positively influence the structural integrity of bone, which may result in an enhancement of bone health.